Gambaran Pasien Katarak dengan Riwayat Diabetes Melitus di Rumah Sakit Mata Bali Mandara - I Gede Ananta Widjaksana; Ni Putu Diah Witari; Ni Nyoman Sunariasih (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
The condition in which the usually clear and clear lens of the eye turns cloudy is called a cataract. In Indonesia, cataracts are the main cause of blindness with a percentage of 77.7%. Data obtained from the Bali Mandara Eye Hospital in 2018 stated that the percentage of cataracts in the province of Bali was 2.7%. Various factors can cause cataracts, diabetes mellitus is one of them. Increased blood sugar levels in patients with diabetes mellitus will provide clearly visible changes in body tissues that are not dependent on insulin for glucose transport. This can occur in the lens of the eye which can cause cataracts. This study aims to determine the description of cataract patients with a history of diabetes mellitus at the Bali Mandara Eye Hospital. This research method is descriptive retrospective with a cross-sectional study design. The data collection method used secondary data from medical records. The research sample was all cataract patients who checked themselves at the Bali Mandara Eye Hospital and met the criteria set by the purposive sampling technique. The data obtained were analyzed univariately. In this study, it was found that patients with cataracts with a history of diabetes mellitus were dominated by female patients and patients with an age range of 50-60 years. Based on the classification suffered, patients with immature cataracts are the most common. Based on the blood sugar levels obtained during the examination, most of the patients had high blood sugar levels.